Unveiling Research Trends in Green Finance in the Age of ESG: A Comprehensive Bibliometric Analysis and Future Research Agenda - El Mortagi, Omar; Belgacem, Ines; SIMMOU, Walid; Ed-Dafali, Slimane; Adardour, Zahra; Gafsi, Nesrine (International Journal of Energy Economics and Policy, 2026)
Green finance has grown significantly over the past thirty years, with the primary aim of protecting the environment and effectively addressing the challenges of climate change through a variety of innovative financial mechanisms and strategies. The present study is designed to conduct a comprehensive bibliometric analysis with the explicit aim of identifying the academic development and diffusion of green finance within the academic community. The literature studied covers the period 1993-2023 from the Scopus database. The results show that the main research topics in this area include the regulation of green credit, the impacts and outcomes of green finance, and strategies for its development. These findings provide insights into green finance research in line with the suggested research trends. Moreover, they identify avenues for future research and provide original insights for managers, investors, and policy-makers to re-compose the climate finance puzzle.